INVESTIGATING CPGA HYDROLASE ACTIVITY OF PARKINSON’S DISEASE-ASSOCIATED DJ-1 MUTANTS - Shkraba, Evelina (Nazarbayev University School of Sciences and Humanities, 2025)
Parkinson’s disease (PD) is the second most common progressive neurodegenerative disease, characterized by symptoms such as tremors, postural instability, bradykinesia, and cognitive impairments. Mutations in PARK7, which encodes DJ-1 protein, are linked to early-onset PD. DJ-1 is a ubiquitously expressed protein with a conserved cysteine residue responsible for its enzymatic activity. Despite extensive research, the precise molecular function of DJ-1 has remained unclear. Recent studies suggest that DJ-1 acts as a hydrolase for the reactive glycolytic metabolite cyclic phosphoglyceric anhydride (cPGA). The present study hypothesizes that mutations in PARK7 gene associated with early-onset PD impair DJ-1’s ability to hydrolyze cPGA. To test this, enzymatic assays are conducted to obtain catalytic constants of wild type and mutant DJ-1. It is shown that the degree of functional impairment correlates with the position of the mutated residue and its effect on active site architecture. Those mutations that are located near the catalytic residues showed drastic impairment, while solvent-exposed residues have no significant reduction of the enzymatic activity compared to the wild type DJ-1. A novel enzymatic assay is used to obtain the catalytic efficiency values. The optimized procedure yields kcat/kM 7.51 × 10⁷ M −1 s −1 , which is 12 times larger than the previously reported activity of wild type DJ-1. Overall, this work demonstrates the biochemical relevance of DJ-1 in Parkinson’s disease neuropathology and directs for future mechanistic and structural studies.
Keywords: DJ-1; Parkinson's Disease; cPGA; catalytic efficiency; enzymatic assay; type of access: embargo